Absence of Blocking Antibody in Non-Inhibitor Haemophilic Plasma - Pool, Judith; Kaelin, A. C (Thrombosis and Haemostasis, 1977)
This study examined the hypothesis that non-inhibitor haemophilic plasma contains antibodies which are specific for sites other than the active procoagulant site on factor VIII, and that some of them might be sufficiently close to the active site that pre-incubation of such plasma with factor VIII would block the subsequent binding of inhibitor antibody. Among the 26 non-inhibitor plasmas examined, none was found to contain such blocking antibody. This result does not eliminate the possibility that antibody is present in such non-inhibitor plasmas which is neither specific for the active enzyme site of factor VIII nor capable of blocking the binding of antibody which does have that specificity.